Social Law 4.0 New Approaches for Ensuring and Financing Social Security in the Digital Age - Becker, Ulrich (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2021)
Digitalisation and the changing world of work are calling into question the standard employment model as a basis for social security systems. Whilst a growing number of publications deal with the consequences for industrial relations and labour law, social law is still being left out of most research projects on digital work. This book aims at widening the perspective. It concentrates on the two most important questions in the context of social protection in a digitalised world, namely access to social protection systems and their future financing, putting emphasis on platform work. It gives an overview of different national approaches to these questions, it analyses the respective solutions in a comparative manner, and it puts them into a transnational context. By bringing together case studies from Belgium, Italy, the United Kingdom, the Netherlands, Denmark, Sweden, Spain, France and Estonia and addressing the specific reform challenges for EU standard setting, EU coordination and the relation to tax law, the book provides new insights on what a "Social Law 4.0" should look like. Digitalisierung und die damit einhergehenden Veränderungen der Arbeitswelt stellen das Standardmodell der Beschäftigung als Basis von sozialen Sicherungssystemen zunehmend in Frage. Während sich eine wachsende Zahl an Veröffentlichungen mit deren Folgen für das Arbeitsrecht beschäftigen, bleibt bis heute das Sozialrecht weitgehend ausgeblendet. Das Buch schafft Abhilfe. Es beschäftigt sich mit den wichtigsten Herausforderungen für den sozialen Schutz durch Digitalisierung, dem Zugang zu Sicherungssystemen und deren Finanzierung am Beispiel der Plattformarbeit. Es gibt einen Überblick über nationale Lösungsansätze, analysiert dies in vergleichender Perspektive und stellt sie in einen transnationalen Kontext. Das Buch vereint Fallstudien aus Belgien, Italien, dem Vereinigten Königreich, den Niederlanden, Dänemark, Schweden, Spanien, Frankreich und Estland und behandelt die Herausforderungen, die Reformen für eine Standardsetzung auf EU-Ebene, für die Koordinierung innerhalb der EU und für ihr Verhältnis zum Steuerrecht ausgesetzt sind. Es vermittelt damit neue Einsichten, wie ein "Sozialrecht 4.0" aussehen sollte.